Thermophilic, anaerobic bacteria isolated from a deep borehole in granite in Sweden. - Szewzyk, U (1994)
A borehole drilled to a total depth of 6779 m in granitic rock in Gravberg, Sweden, was sampled and examined for the presence of anaerobic, thermophilic, fermenting bacteria and sulfate-reducing bacteria. Growth in enrichment cultures was obtained only from water samples collected from a specific sampling depth in the borehole (3500 m). The hole was cased down to a depth of 5278 m and open to the formation below that level. All the water below 2000 m in depth standing in the borehole at the time of sampling must have entered at the 5278-m level or below, during a prior pumping operation. A strong salinity stratification certifies that no major amount of vertical mixing had taken place. The depth from which bacteria could be enriched was that of a pronounced local minimum of salinity. Pure cultures of thermophilic, anaerobic, fermenting bacteria were obtained with the following substrates: glucose, starch, xylan, ethanol, and lactate. The morphology and physiology of the glucose- and starch-degrading strains indicate a relationship to Thermoanaerobacter and Thermoanaerobium species. All but one of the newly isolated strains differ however from those by lacking acetate as a fermentation product. The glucose-degrading strain Gluc1 is phylogenetically related to Clostridium thermohydrosulfuricum, with an evolutionary distance based upon rRNA sequence comparisons of 3%. No sulfate-reducing or methanogenic bacteria were found.